A Structurally Characterized Fluoroalkyne. Issue 26 (23rd May 2017) - Hall, Lewis M.; Tew, David P.; Pridmore, Natalie E.; Whitwood, Adrian C.; Lynam, Jason M.; Slattery, John M.
Abstract: The facile synthesis of a stable and isolable compound with a fluoroalkynyl group, M−C≡CF, is reported. Reaction of [Ru(C≡CH)(η 5 ‐C5 Me5 )(dppe)] with an electrophilic fluorinating agent (NFSI) results in the formation of the fluorovinylidene complex [Ru(=C=CHF)(η 5 ‐C5 Me5 )(dppe)][N(SO2 Ph)2 ]. Subsequent deprotonation with LiN(SiMe3 )2 affords the fluoroalkynyl complex [Ru(C≡CF)(η 5 ‐C5 Me5 )(dppe)]. In marked contrast to the rare and highly reactive examples of fluoroalkynes that have been reported previously, this compound can be readily isolated and structurally characterized. This has allowed the structure and bonding in the CCF motif to be explored. Further electrophilic fluorination of this species yields the difluorovinylidene complex [Ru(C=CF2 )(η 5 ‐C5 Me5 )(dppe)][N(SO2 Ph)2 ]. Abstract : Fancy a fluorine? In contrast to other fluorinated alkynes, structurally characterized M−C≡CF exhibits considerable long‐term stability. Structural, spectroscopic and computational analyses reveal that this longevity is underpinned by kinetic stabilization by a half‐sandwich ruthenium substituent. Subsequent fluorination provides facile access to a rare example of a difluorovinylidene complex.